(untitled) (Journal of International Studies, 2020)
Myanmar is moving rapidly in the direction of a more democratic and economically strong future. However, many challenges remain and constructive change will require the cooperation of the corporate sector. Many foreign businesses are interested in investing in Myanmar as a result of political reforms. The government could take a pivotal role, leading the agenda by setting Corporate Social Responsibility (CSR) standards as a tool for social development. This paper explores how CSR could be embedded in government business strategy, how business practice could exceed public expectations, how labour laws could strengthen employee packages and benefits, and how foreign investors could be encouraged to bring CSR expertise to strengthen domestic capabilities. Finally, this paper argues that a CSR code of conduct should be imposed to ensure that business practices are tailored to national economic and social interests, and the form such a code of conduct could take.